A 5:2 intermittent fasting regimen ameliorates NASH and fibrosis and blunts HCC development via hepatic PPARα and PCK1 - Gallage, Suchira; Ali, Sheikh Adnan; Barragan Avila, José Efren; Seymen, Nogayhan; Ramadori, Pierluigi; Joerke, Vera; Zizmare, Laimdota; Aicher, David; Gopalsamy, Indresh K.; Fong, Winnie; Kosla, Jan; Focaccia, Enrico; et al. (Cell metabolism, 2024)
The role and molecular mechanisms of intermittent fasting (IF) in non-alcoholic steatohepatitis (NASH) and its transition to hepatocellular carcinoma (HCC) are unknown. Here, we identified that an IF 5:2 regimen prevents NASH development as well as ameliorates established NASH and fibrosis without affecting total calorie intake. Furthermore, the IF 5:2 regimen blunted NASH-HCC transition when applied therapeutically. The timing, length, and number of fasting cycles as well as the type of NASH diet were critical parameters determining the benefits of fasting. Combined proteome, transcriptome, and metabolome analyses identified that peroxisome-proliferator-activated receptor alpha (PPARα) and glucocorticoid-signaling-induced PCK1 act co-operatively as hepatic executors of the fasting response. In line with this, PPARα targets and PCK1 were reduced in human NASH. Notably, only fasting initiated during the active phase of mice robustly induced glucocorticoid signaling and free-fatty-acid-induced PPARα signaling. However, hepatocyte-specific glucocorticoid receptor deletion only partially abrogated the hepatic fasting response. In contrast, the combined knockdown of Ppara and Pck1 in vivo abolished the beneficial outcomes of fasting against inflammation and fibrosis. Moreover, overexpression of Pck1 alone or together with Ppara in vivo lowered hepatic triglycerides and steatosis. Our data support the notion that the IF 5:2 regimen is a promising intervention against NASH and subsequent liver cancer.